Proteomic analysis of adipose tissue: informing diabetes research. (August 2014) - Murri, Mora; Insenser, María; Luque, Manuel; Tinahones, Francisco J; Escobar-Morreale, Héctor F
Abstract : Diabetes, one of the most common endocrine diseases worldwide, results from complex pathophysiological mechanisms that are not fully understood. Adipose tissue is considered a major endocrine organ and plays a central role in the development of diabetes. The identification of the adipose tissue-derived factors that contribute to the onset and progression of diabetes will hopefully lead to the development of preventive and therapeutic interventions. Proteomic techniques may be useful tools for this purpose. In the present review, we have summarized the studies conducting adipose tissue proteomics in subjects with diabetes and insulin resistance, and discussed the proteins identified in these studies as candidates to exert important roles in these disorders.